DAMPAK POLA ASUH ORANG TUA DALAM PEMAKNAAN SIKAP SOPAN SANTUN ANAK USIA SEKOLAH DASAR - Elma Elfiana Nurus; Sekar Dwi Ardianti; Imaniar Purbasari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to determine and describe the impact of parenting on signifying polite attitudes for elementary school-aged children. This research utilized descriptive qualitative research. The subjects of this study were four children and four parents. This study was carried out in Desa Sumbersari, Kecamatan Kayen Kabupaten Pati. Data collection techniques and instruments used in this study were observation, interviews and documentation. The data were analyzed through qualitative data analysis with reference to the concept of Miles and Huberman. The results of this study indicated that there was an impact on each parent’s parenting style.Different parenting patterns resulted in different parenting effects. Children with authoritarian parenting showed a lack of manners in actions and language. Children with permissive parenting demonstrated a lack of politeness in language, but possessed a good manners of action. Lastly, children with democratic parenting showed language politeness and good actions.